The state of Philippine democracy 1987 - Brillantes, Alex B., Jr (Philippine Journal of Public Administration, 1987)
The assumption of President Aquino to the Presidency has seen the installation of a number of structures and processes that supposedly constitute the restoration of democracy to the country. These include the Constitution, Congress, electoral processes and political parties among other things. However, caution must be exercised lest these become the mere formalisms of democracy.